Mechanical performance of composite bonded joints in the presence of localised process-induced zero-thickness defects - Yazdani Nezhad, Hamed; Stratakis, Dimosthenis; Ayre, David; Addepalli, Sri; Zhao, Yifan (Elsevier, 2018)
Processing parameters and environmental conditions can introduce variation into the performance of adhesively bonded joints. The effect of such variation on the mechanical performance of the joints is not well understood. Moreover, there is no validated non-destructive inspection (NDI) available to ensure bond integrity post-process and in-service so as to guarantee initial and continued airworthiness in aerospace sector. This research studies polymer bond defects produced in the laboratory scale single-lap composite-to-composite joints that may represent the process-induced defects occurring in actual processing scenarios such as composite joining and repair in composite aircrafts. The effect of such defects on the degradation of a joint’s mechanical performance is then investigated via quasi-static testing in conjunction with NDI ultrasonic C-scanning and pulsed thermography. This research is divided into three main sections: 1- manufacturing carbon fibre-reinforced composite joints containing representative nearly zero-thickness bond defects, 2- mechanical testing of the composite joints, and 3- assessment of the NDI capability for detection of the bond defects in such joints.
Keywords: composite joint; adhesive bonding; airworthiness; bond degradation; non-destructive inspection; cohesive failure